THE USE OF CODE SWITCHING AND CODE MIXING IN EXTENSIVE READING CLASS AT UNIVERSITAS PGRI RONGGOLAWE TUBAN - Pratama, Dandy Putra; Umar, Moch.; Triassanti, Risa (Prosiding SNasPPM, 2022)
This study aims to determine the type of code switching and the type of code mixing used at extensive reading class at Universitas PGRI Ronggolawe Tuban. The study applied qualitative research design. The aims of this study was to analyse the types and the most used code switching and code mixing. Participants in this study were lecturer and students at extensive reading class in Universitas PGRI Ronggolawe Tuban. The class contains 21 students from the 2018 class and 1 teaching lecturer. Data collection in this study was carried out by a voice recorder on a smart phone. From these data, the types and the most used of code switching and code mixing might be identified. Furthermore, there are several types of code switching namely intersentential code switching, intrasentential code switching, and tag switching. The next are the types of code mixing namely alternation, insertion, and congruent lexicalization. The results is two types of code switching that are found in the Extensive reading class are inter sentential switching and intra sentential switching. One type of code mixing that is found in the Extensive reading class is alternation. And the most used is code switching type inter sentential switching.